A pilot study on early home-based intervention through an intelligent baby gym (CareToy) in preterm infants. (June 2016) - Sgandurra, Giuseppina; Bartalena, Laura; Cecchi, Francesca; Cioni, Giovanni; Giampietri, Matteo; Greisen, Gorm; Herskind, Anna; Inguaggiato, Emanuela; Lorentzen, Jakob; Nielsen, Jens Bo; Orlando, Martina; Dario, Paolo; et al.
Highlights: CareToy is an intelligent baby gym for tele-monitored home intervention in infancy. Rehabilitation staff can individualize the training provided by CareToy system. CareToy intervention is feasible in 3–9 months old preterm born infants. The intervention was well accepted by parents and infants. CareToytraining was associated with a higher motor and visual development. Abstract: Background: CareToy is an intelligent system, inspired by baby gyms, aimed to provide an intensive, individualized, home-based and family-centred early intervention (EI) program. Aims: A pilot study was carried out to explore the feasibility of CareToy intervention in preterm infants, aged 3–9 months of corrected age. Methods: Twenty low-risk preterm infants, without brain lesion or other clinical complications (14 allocated to CareToy intervention and 6 to Standard Care) were recruited. The Infant Motor Profile (IMP) was predefined as the primary outcome measure and Alberta Infant Motor Scale and Teller Acuity Cards as secondary measures. Moreover, 202 pre-programmed training scenarios were developed and instructions for the management of CareToy intervention were defined as general guidelines. Outcomes and results: All infants received 4 weeks of their allocated intervention and were evaluated with the selected tests before and immediately after the 4 weeks. The mean difference changes in IMP total score and Teller Acuity Cards over the intervention period were higher in the CareToy group than in the Standard Care group. Conclusions and implications: CareToy seems a feasible device for providing EI. An adequately powered randomized clinical trial is warranted.